COMPOSITION AND TAXONOMIC DIVERSITY OF PLANTS IN GARKI VILLAGE, BAURE LOCAL GOVERNMENT, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The importance of plants to man cannot be overemphasized. Beyond their value for food, energy and fiber, plants act as cleanser by filtering pollutants such as oxides of carbon, toxic gases and heavy metals. This study assessed the composition and taxonomic distribution of plants with a view to providing informationfor the development of sustainable production options in the study area. Vegetation sampling was employed in this study to count, list and identify plants. A 50m2 quadrat was used based on the information obtained about the floristic composition of the study during reconnaissance. Result of the study showed that a total of thirty plants comprising of trees, shrubs and herbs were recorded in the area. These plants belong to 20 families. The Caesalpiniaceae, Fabaceae and Palmae were represented by the highest number of species while Convolvulaceae, Solanaceae, Eurphobiaceae, Asteraceae, Meliceae and Bombaceae have only one member respectively. The study area was composed of twenty two trees (65%), five shrubs (20%) and seven herbs (15%) hence it is woody in nature. This study recommended participatory management of species composition and diversity by strengthening local communities’ abilities to develop sense of ownership and responsibility for the management and conservation of species in areas. This can be achieved through the expos, exhibitions and use electronic media and ICT (mobile devices)
Keywords: floristic composition, biodiversity, conservation, sustainable production